Intelligent trading/metering/billing system ITMBS-II-B wireless network and system design - Ho, Wei Jie. (2009)
As the Singapore government started on reducing its control on the electricity market, more electricity retailers are entering the electricity market. The increased competition from the new retailers will promote the prices of electricity to be more competitive and consumers can expect better customer services. However the current system of tracking energy consumption using electro-mechanical meters is unable to meet the requirements of the new energy market in Singapore. Hence this project aims at the development of an intelligent trading meter billing system (ITMBS) to meet the requirements of the new deregulated power market environment.